(untitled) (Journal of the College of Basic Education, 2022)
Organization must take significant investment to protect the electronic documents that contain mission-critical, personal, and sensitive information.Many information security solutions attempt to protect electronic documents only on their storage location or during transmission. The purpose of this paper is intended to provide the reader with a brief overview of relevant document security issues and technologies as well as to introduce a proposed method for persistent security for electronic document throughout its lifecycle. Several security requirements such as confidentially, authorization, accountability, integrity, authenticity, and non-repudiation must be met to provide more effective protection for electronic document throughout its lifecycle. These requirements can be achieved by using the followings: a) Document Control process: which can be achieved confidentially, authorization, and accountability by using encryption technique.b) Digital signature technique: which can be achieved integrity, authenticity, and non-repudiation by using secure hash algorithm-1(SHA-1) and encryption technique.